Fault Detection Enhancement in Rolling Element Bearings Using the Minimum Entropy Deconvolution - BARSZCZ, Tomasz; SAWALHI, Nader (Archives of Acoustics, 2012)
Minimum Entropy Deconvolution (MED) has been recently introduced to the machine condition mon-itoring field to enhance fault detection in rolling element bearings and gears. MED proved to be anexcellent aid to the extraction of these impulses and diagnosing their origin, i.e. the defective componentof the bearing. In this paper, MED is revisited and re-introduced with further insights into its applicationto fault detection and diagnosis in rolling element bearings. The MED parameter selection as well as itscombination with pre-whitening is discussed. Two main cases are presented to illustrate the benefits ofthe MED technique. The first one was taken from a fan bladed test rig. The second case was taken from awind turbine with an inner race fault. The usage of the MED technique has shown a strong enhancementfor both fault detection and diagnosis. The paper contributes to the knowledge of fault detection of rollingelement bearings through providing an insight into the usage of MED in rolling element bearings diag-nostic. This provides a guide for the user to select optimum parameters for the MED filter and illustratesthese on new interesting cases both from a lab environment and an actual case.